2014
DOI: 10.5339/connect.2014.23
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of innovation in Qatar and its transition to knowledge-based economy: Relative strengths and weaknesses

Abstract: Qatar, as the most competitive economy in the region, seeks the transition to a knowledge-based economy. Innovation plays a crucial role in the economic development transform stage (from a resource-based to a knowledge-based economy) promising a more sustainable future. Hence, this paper presents a descriptive study of the status quo of Qatar in innovation and considers its domestic innovation dynamics through the Global Innovation Measure (Index) data, while also comparing Qatar to Switzerland as the world le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 7 publications
1
9
0
Order By: Relevance
“…Both business sophistication and knowledge and technology outputs are directly linked to innovation activities and are part of the GII. Consequently, a previous descriptive study of the innovation status quo in Qatar assessed its domestic innovation dynamics through the GII data while also comparing it to Switzerland, ranked as the world's leading economy with a complete Innovation Efficiency Ratio (100%) in the same index [41]. They found that Qatar has shown a promising start toward economic development in recent years and that Qatar's scores are excellent in some areas, which aligned with this study findings.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Both business sophistication and knowledge and technology outputs are directly linked to innovation activities and are part of the GII. Consequently, a previous descriptive study of the innovation status quo in Qatar assessed its domestic innovation dynamics through the GII data while also comparing it to Switzerland, ranked as the world's leading economy with a complete Innovation Efficiency Ratio (100%) in the same index [41]. They found that Qatar has shown a promising start toward economic development in recent years and that Qatar's scores are excellent in some areas, which aligned with this study findings.…”
Section: Discussionsupporting
confidence: 81%
“…Consequently, to study the innovation dynamics of Qatar's entrepreneurial ecosystem, it is relevant to consider existing indicators such as the GII, which indicates that the country is performing below expectations considering it has one of the highest GDP per capita in the world. A previous descriptive study of the innovation status quo in Qatar assessed its domestic innovation dynamics through the GII data while also comparing it to Switzerland, ranked as the world's leading economy with a complete Innovation Efficiency Ratio (100%) in the same index [41]. Composed of seven pillars, the GII highlights Qatar's strengths and weaknesses, with business sophistication showing the weakest performance and infrastructure the best [39].…”
Section: The Qatari Contextmentioning
confidence: 99%
“…Both cases confirm the importance of government interventions in the knowledge-based economy. Governments contribute a great deal in the transition toward a knowledge-based economy by building efficient institutions, investing in IT infrastructure, a highly competitive entrepreneurial environment and education system (Faghih and Sarfaraz, 2014). Macroeconomic policies, good governance and a business-friendly climate provide the basis for knowledge-based economy strategies.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the youth unemployment rate reached about 25%. More than half of Iran's population are youth, as the major contributors to the economy and entrepreneurship seek a transition to a knowledge-based economy (Faghih and Sarfaraz, 2014). Given its big and youthful population as well as good capital stocks and resources, Iran certainly could become an entrepreneurial and economic powerhouse, also given Iranians' appreciation and investment in education (Ratten et al, 2016).…”
Section: Transitional Entrepreneurship In Distressed Economy Of Iranmentioning
confidence: 99%